Mycelial and secretome proteomic dynamics of L. squarrosulus AF5 in azo dye degradation. Issue 2 (April 2023) - Mathur, Anshu; Dubey, Swati; Prasad, Ramasre; Singh, Rajesh Pratap
Abstract: Mycoremediation of textile effluents is a practical and eco-friendly approach for mineralizing synthetic dyes. The textile, food processing, chemical, leather, dyestuff, dyeing, and pharmaceutical industries discharge significant amounts of effluents including different types of dyes. One of the largest manufacturers of dyes is the textile industry, and dyes discharged from these industries directly affect the natural ecosystem by entering in to the soil and water. These industries release effluents that are carcinogenic and pose a potential threat to flora and fauna. Distinct fungal species are identified as dye decomposers because these can produce a variety of extracellular enzymes involved in catabolism. The strain isolated from the dye effluents was identified as Lentinus squarrosulus AF5 and had a remarkable ability for decolorization (50–96 %) within 72 h using a dye mix consisting of AB10B, RB5, and RB160 (500 mg L -1 . The dynamics of the protein profile was deciphered using gel-free/label-free nLC-MS/MS analysis. Distinct protein profiles in the mycelial extract of Lentinus squarrosulus AF5 were observed following exposure of the strain with dyes mix. About 90 proteins have been depicted by proteomic analysis wherein 10 proteins appear to be differentially expressed during dye treated conditions. Secretome proteome had denoted 13 proteins under similar conditions. Notable levels of manganese peroxidase (258.84 ± 0.001 U/ml) along with relatively lower levels of lignin peroxidases (194.98 ± 0.002 U/ml) and laccase (134.33 ± 0.007 U/ml) were detected during dye treated condition, suggesting thereby the extracellular peroxidases displaying a pivotal role in decolorization process. The UV-Visible, FTIR spectroscopic along with HPLC and LC-QTOF-MS analyses of the dye supernatants following incubation with Lentinus squarrosulus AF5 had indicated the degradation of the dyes. These observations suggest Lentinus squarrosulus AF5 to be a potential strain for the catabolism of azo dyes. Graphical Abstract: ga1 Highlights: Lentinus squarrosulus AF5 showed notable dye decolorization ability for mixed dyes. Mixed dyes showed ∼96% of decolorization was achieved after 72 h of incubation. The dynamics of the protein profile were deciphered by nLC-MS to identify upregulated molecular factors. MnP and LiP, Lac were the major extracellular peroxidases in the decolorization process. LC-QTOF-MS analysis was used to identify the degraded products of azo dyes.